Profile of professional musicians in Rio de Janeiro (1943-1945): an exploratory study (Orfeu, 2024)
Through this article, we intend to understand the formation of the musical workers category that worked professionally in Rio de Janeiro in the 1940s. To do so, we use the registration of musicians in the documentary fund of the former Customs and Entertainment Police Station, currently under the custody of the National Archive.  Based on statistical investigation of registration covering the years 1943 to 1945, we established the characteristics of this labor category in terms of age, gender, race, marital status, education, place of birth, lenght of time workin in music, exclusive subsistence through  music, among others.  We also use the repositories of the Musical Center of Rio de Janeiro (1907-1941) and the Syndicate of Professional Musicians of Rio de Janeiro (1941-), in order to establish the link between these artists and their class syndicate.  With the Getulio Vargas government as a backdrop, a period marked by the implementation of structuring policies in the national labor field, it is possible to see how musicians and these entities were integrated into governement policies.
Keywords: music and work; Customs and Entertainment Police Station; Musical Center of Rio de Janeiro; Syndicate of Pro-fissional Musicicians of Rio de Janeiro